The Current State-of-the Art of LRRK2-Based Biomarker Assay Development in Parkinson’s Disease - Rideout, Hardy J.; Chartier-Harlin, Marie-Christine; Fell, Matthew J.; Hirst, Warren D.; Huntwork-Rodriguez, Sarah; Leyns, Cheryl E. G.; Mabrouk, Omar S.; Taymans, Jean-Marc (Frontiers in Neuroscience, 2020)
Evidence is mounting that LRRK2 activity, particularly its kinase activity, is elevated in multiple forms of Parkinson’s disease, both idiopathic as well as familial forms linked to mutations in the LRRK2 gene. However, sensitive quantitative markers of LRRK2 activation in clinical samples remain at the early stages of development. There are several measures of LRRK2 activity that could potentially be used in longitudinal studies of disease progression, as inclusion/exclusion criteria for clinical trials, to predict response to therapy, or as markers of target engagement. Among these are levels of LRRK2, phosphorylation of LRRK2 itself, either by other kinases or via auto-phosphorylation, its in vitro kinase activity, or phosphorylation of downstream substrates. This is advantageous on many levels, in that multiple indices of elevated kinase activity clearly strengthen the rationale for targeting this kinase with novel therapeutic candidates, and provide alternate markers of activation in certain tissues or biofluids for which specific measures are not detectable. However, this can also complicate interpretation of findings from different studies, if one study reports changes in LRRK2 function by one measure, and another uses a different one. In this review we discuss the current state of LRRK2-focussed biomarkers, what are the advantages and disadvantages of the current pallet of outcome measures, what gaps remain to be filled, and what priorities the field has defined.